Incorporation of a sequential BMP-2/BMP-7 delivery system into chitosan-based scaffolds for bone tissue engineering - Yilgor, Pinar (2009)
The aim of this study was to develop a 3-D construct carrying an inherent sequential growth factor delivery system. Poly(lactic acid-co-glycolic acid) (PLGA) nanocapsules loaded with bone morphogenetic protein BMP-2 and poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) nanocapsules loaded with BMP-7 made the early release of BMP-2 and longer term release of BMP-7 possible. 3-D fiber mesh scaffolds were prepared from chitosan and from chitosan–PEO by wet spinning. Chitosan of 4% concentration in 2% acetic acid (CHI4–HAc2) and chitosan (4%) and PEO (2%) in 5% acetic acid (CHI4– PEO2–HAc5) yielded scaffolds with smooth and rough fiber surfaces, respectively. These scaffolds were seeded with rat bone marrow mesenchymal stem cells (MSCs). When there were no nanoparticles the initial differentiation rate was higher on (CHI4–HAc2) scaffolds but by three weeks both the scaffolds had similar alkaline phosphatase (ALP) levels. The cell numbers were also comparable by the end of the third week. Incorporation of nanoparticles into the scaffolds was achieved by two different methods: incorporation within the scaffold fibers (NP–IN) and on the fibers (NP–ON). It was shown that incorporation on the CHI4–HAc2 fibers (NP–ON) prevented the burst release observed with the free nanoparticles, but this did not influence the total amount released in 25 days. However NP–IN for the same fibers revealed a much slower rate of release; ca. 70% released at the end of incubation period. The effect of single, simultaneous and sequential delivery of BMP-2 and BMP-7 from the CHI4–HAc2 scaffolds was studied in vitro using samples prepared with both incorporation methods. The effect of delivered agents was higher with the NP–ON samples. Delivery of BMP-2 alone suppressed cell proliferation while providing higher ALP activity compared to BMP-7. Simultaneous delivery was not particularly effective on cell numbers and ALP activity. The sequential delivery of BMP-2 and BMP-7, on the other hand, led to the highest ALP activity per cell (while suppressing proliferation) indicating the synergistic effect of using both growth factors holds promise for the production of tissue engineered bone.